ANALISIS MODEL MENTAL SISWA MENGGUNAKAN TES DIAGNOSTIK MODEL MENTAL TWO-TIER (TDM-TWO-TIER) PADA MATERI LAJU REAKSI - Armawita Armawita; Heppy Okmarisa (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2020)
AbstractThis research was instigated by student mental model that was not intact on Reaction Rate lesson.  It aimed at analyzing and knowing student mental model through Two-Tier (TDM-Two-Tier) Mental Model Diagnostics Test instrument (TDM-Two-Tier) on Reaction Rate lesson at State Senir High School 2 Pekanbaru.  This research was conducted at the first semester in the Academic Year of 2019/2020.  It was Descriptive quantitative research.  The data in this research were collected by Two-Tier (TDM-Two-Tier) Mental Model Diagnostics Test instrument, interview, and documentation.  The collected data were analyzed by using Descriptive analysis.  Purposive Sampling technique was used in this research.  The samples of this research were 36 students at the eleventh grade of MIPA 2 of State Senior High School 2 Pekanbaru.  The research findings showed that student mental model was not intact.  It could be seen from the mean score of student mental model that was obtained from TDM-Two-Tier Diagnostics Test, Scientifically Correct (SC) of intact mental model or Scientifics was 47%, Partially Correct (PC) or partial mental model or alternative was 48%, students were able to understand the macroscopic level was 12%, symbolic level was 17% and submicroscopic level was 19% and Specific Misconception (SM) or misconception was 5%.  Keywords: Mental Model, TDM-Two-Tier, Reaction Rate